Parameter Menentukan Perbuatan Wanprestasi Dan Penipuan Dari Suatu Perjanjian - Azhari Ar Azhari Ar (Universitas Islam Sumatera Utara, 2020)
Agreement is made legally binding for the makers and the parties are obliged to fulfill it. In the practice of daily life, it is not uncommon for contract actors who do not carry out their obligations; they are being prosecuted by creditors through criminal law by referring to article 378 of the Criminal Code so that there seems to be a similarity between the default legal figure and fraud in an agreement, whereas in the regulation both of these are governed by different laws. Default is regulated in the Civil Code while fraud is regulated in the Criminal Code. The problem in this paper is what is the parameter or measure to determine the legal acts of default and criminal act of fraud.Distinguishing parameter between default and fraud is on the default which is seen from the objective and subjective factors of good faith, while the criminal act of fraud is motivated by evil intentions (mens rea) to have an object (items) belonging to someone else with the parameters of subjective and objective elements. In the future, law practitioners and academics should be able to separate explicitly to settle dispute agreements that contain defaults and criminal act of fraud.